Targeting Educational Quality: The Role of Educator Management Transformation in Enhancing Services - Luluk Ahman Suro; Aprillia Fentika Dewi Gita Anggraeni (Al-Qalam Institute, 2024)
This study explores the role of educator management in improving the quality of education at Madrasah Aliyah focusing on key factors such as educator professionalism, leadership, and collaboration between educators, students, and parents. The purpose of this research is to examine how the transformation of educator management, particularly through professional development and leadership, impacts educational outcomes. The study adopts a qualitative approach with a case study design, using data collected from observations, interviews, and documentation. The findings indicate that continuous professional development, including pedagogical training and technology integration, significantly enhances educator competency, leading to more effective teaching practices. Furthermore, the leadership of the school principal plays a crucial role in shaping the educator management process, where clear vision, participatory decision-making, and transparent communication foster collaboration among educators and motivate them to improve their performance. Additionally, the study highlights the importance of collaboration between educators, students, and parents, as it strengthens communication, increases parental involvement, and ultimately boosts student motivation and academic achievement. These findings suggest that developing a collaborative and well-managed educational environment can lead to better student learning outcomes.